Analysis Of The Impact Of Special Autonomy Funds/Privileges On Health And Education Spending On HDI In Special Autonomy Regions - Iqbal Nurfansyah; Azansyah Azansyah (Journal of Islamic Economics and Finance, 2024)
The real source of a country's riches and an essential component of its development are its people. We can determine the extent to which human resources are of high quality from the perspectives of the economy, health, and education thanks to the HDI. DKI Jakarta is the province in Indonesia with the highest HDI, while Papua and West Papua have the lowest HDIs. Both provinces get special funding known as special autonomy funds and are recognized as special autonomous areas. Even after Papua was given special autonomy funds twenty years ago, it is still the province in Indonesia with the lowest HDI. Improving the Human Development Index (HDI) mostly depends on spending in the areas of economy, health, and education. This study looks at the impact of spending on the economy, health, and education as well as local government expenditure (DOK) on the HDI. Using secondary data from the Directorate General of Fiscal Balance (DJPK) and the Central Statistics Agency (BPS), panel data regression is the study methodology employed. The study's findings show that DOK has a favorable impact on the HDI, as does spending on the economy, health, and education